2013
DOI: 10.1007/s00167-013-2422-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined arthroscopic deepening trochleoplasty and reconstruction of the medial patellofemoral ligament for patients with recurrent patella dislocation and trochlear dysplasia

Abstract: Prospective consecutive case series, with evaluation of confounding factor. No control group, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 49 publications
5
74
0
3
Order By: Relevance
“…In the second publication, which was a follow-up study of a consecutive series of 29 knees in patients troubled by patella instability and treated by combined ADT and MPFL reconstruction, we found significantly improved median knee scores for all measured parameters with no redislocations. 20 These results have been confirmed in a more recent review including 18 more knees. 27 Since 2008, we have allowed full weight bearing after the operation.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In the second publication, which was a follow-up study of a consecutive series of 29 knees in patients troubled by patella instability and treated by combined ADT and MPFL reconstruction, we found significantly improved median knee scores for all measured parameters with no redislocations. 20 These results have been confirmed in a more recent review including 18 more knees. 27 Since 2008, we have allowed full weight bearing after the operation.…”
Section: Discussionmentioning
confidence: 59%
“…No redislocations have been reported. The results from the first 29 cases have been published, 20 in which significant improvements in Kujala and Knee injury and Osteoarthritis Outcome (KOOS) scores were observed with 93% of patients reporting satisfaction with the outcome and 55% returning to sports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Banke et al 42 also noted in their series of combined trochleoplasty and MPFL reconstruction that 2 out of 18 cases developed arthrofibrosis, which was successfully treated with early arthroscopic arthrolysis. However, other studies [43][44][45] have reported no cases of arthrofibrosis in their series. In a systematic review of 17 studies in 459 knees, Song et al 41 found greater range of motion deficits in the group that underwent trochleoplasty.…”
Section: Mpfl Reconstructionmentioning
confidence: 80%